Observations of microphysical properties and radiative effects of contrail cirrus and natural cirrus over the North Atlantic - Wang, Ziming; Bugliaro Goggia, Luca; Jurkat-Witschas, Tina; Heller, Romy; Burkhardt, Ulrike; Ziereis, Helmut; Dekoutsidis, Georgios; Wirth, Martin; Groß, Silke Martha; Kirschler, Simon; Kaufmann, Stefan; Voigt, Christiane (Atmospheric Chemistry and Physics, 2023)
Contrail cirrus constitute the largest radiative forcing (RF) component of the aviation effect on climate. However, the difference of microphysical properties and radiative effects between contrails, contrail cirrus and natural cirrus clouds are still not completely resolved. Motivated by these uncertainties, we investigate the cirrus perturbed by aviation in the North Atlantic Region on 26 March 2014 during the Mid Latitude Cirrus (ML CIRRUS) experiment. In the synoptic context of a ridge cirrus cloud, an extended thin ice cloud with many persistent contrails can be observed for many hours with the geostationary Meteosat Second Generation (MSG)/Spinning Enhanced Visible and InfraRed Imager (SEVIRI) from the morning hours until dissipation close to 14 UTC. Airborne lidar observations aboard the German High Altitude and LOng Range Research Aircraft (HALO) suggest that this cloud is mainly of anthropogenic origin.